Strategies to Favor Integral Learning and Development Based on the Study of Physics in Preschool - Peña, Natalia Contreras; Díaz, Mario Humberto Ramírez; Mendoza, Juan Carlos Ruiz (South Eastern European Journal of Public Health, 2024)
Considering the New Educational Model for Preschool Education in Mexico, a proposal is developed to favor the early stimulation of learning with the use of simple machines: balance, ramp and pulley as a means to develop preconceptions of mathematical thinking in children, incorporating play with the objective of favoring the participation of students through science, particularly physics. The experience was carried out in a kindergarten in Mexico City and consisted of a diagnosis of the children's level of development in the five fields of the New Educational Model for Preschool Education in Mexico, the design and implementation of play activities with physics content, and the monitoring of the results.